Adolescents' Unhealthy Eating Behavior and Customer Engagement on Social Media in Sub-Urban Areas: Adolescents’ Unhealthy Eating Behavior and Customer Engagement on Social Media in Sub Urban Areas - A'yunin, Elia Nur; Mustakim, Mustakim; Arumsari, Imas (Amerta Nutrition, 2024)
Background: Social media exposure is one of the effective strategies for digital marketing of food and beverage products in this present era. In addition, adolescents are the dominant users of social media (75.5%), which affects their behavior and health status. Objectives: This study aimed to describe adolescent eating behavior and customer engagement with food, beverage, and drink-related content on social media in sub-urban areas and to analyze the relationship with their eating behavior. Methods: The procedures were carried out using a descriptive observational method with a cross-sectional approach at SMA XX in the sub-urban areas in Depok City. The participants comprised class X aged 15-16 years (n=277) who were selected using the total sampling method. In addition, adolescents' healthy eating behavior was measured by AFHC (Adolescent Food Habits Checklist). The data obtained were then analyzed using an independent T-test with a Confidence Interval (CI) of 95%. Results: The results showed that the majority of the participants had unhealthy eating behavior. In addition, two aspects of customer engagement behavior showed a significant relationship with healthy eating in adolescents. This behavior includes liking and commenting on food and drink advertisements/promotions on social media (p-value=0.051), sharing, reposting, or tagging someone in food and drink content, reviews of places to eat, or viral food trends (p-value=0.025). Conclusions: Customer engagement on social media significantly affected eating behavior of adolescents in sub-urban areas, particularly behavior of liking and sharing/reposting food adverts.